Teknologi Tepat Guna Mesin Irat Bambu untuk Meningkatkan Produksi Bagi Pengrajin Bambu Gedek di Desa Karanganom, Kec. Klaten Utara, Kab. Klaten, Prop. Jawa Tengah - Sumpena; Jemadi (Politeknosains, 2017)
The purpose of using bamboo depletion machine is to increase the quantity and quality of bamboo depletion production for gedek bamboo craftsmen. Bamboo depletion machine is a machine that works to attenuate bamboo with the thickness that can be arranged as needed. This machine is used to help small entrepreneurs produce bamboo depletion products in large quantities by saving time and labor. The working principle of this engine is a motor gasoline as a driving force to generate power and rotation that is transmitted through pulleys and belts to the shafts with the aid of gears on each axle to rotate the roller. After roller rotate will produce a tensile force that will be used to pull the bamboo to the knife so that there bamboo depletion process. The experimental results show that this bamboo depletion machine has an average capacity of 224 layers / hour. Dimension of bamboo depletion machine with specification: P 600 mm, L 600 mm, T 1200 mm, iron plate material, power motor drive 5,5 PK. So that the productivity and quality of products made of bamboo can be the same and uniform according to consumer standards.